Single shot i-Toffoli gate in dispersively coupled superconducting qubits - Baker, Aneirin J.; Huber, Gerhard B. P.; Glaser, Niklas J.; Roy, Federico; Tsitsilin, Ivan; Filipp, Stefan; Hartmann, Michael (Applied Physics Letters, 2022)
Quantum algorithms often benefit from the ability to execute multi-qubit (> 2) gates. To date, such multi-qubit gates are typically decomposed into single- and two-qubit gates, particularly in superconducting qubit architectures. The ability to perform multi-qubit operations in a single step could vastly improve the fidelity and execution time of many algorithms. Here, we propose a single shot method for executing an i-Toffoli gate, a three-qubit gate with two control and one target qubit, using currently existing superconducting hardware. We show numerical evidence for a process fidelity over 99.5% and a gate time of 450 ns for superconducting qubits interacting via tunable couplers. Our method can straight forwardly be extended to implement gates with more than two control qubits at similar fidelities.
CRIS-Team WoS Importer:2022-03-18